1999
DOI: 10.1139/y99-033
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial meta-[125I]iodobenzylguanidine uptake in awake genetically hypertensive rats at different ages: an autoradiographic study

Abstract: The purpose of this work was to evaluate changes in myocardial meta-[125I]iodobenzylguanidine ([125I]MIBG) uptake and distribution with age in awake spontaneously hypertensive rats (SHR) with respect to Wistar-Kyoto (WKY) rats. Rats were randomly divided into two groups, one for measuring myocardial [125I]MIBG uptake and distribution 4 h after its injection and the second for evaluating myocardial catecholamine concentrations. Mean arterial blood pressure, cardiac hypertrophy index (heart/body weight ratio), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The result indicated that the hypertrophied heart in SHRs becomes heavier during the progression of LVH, which is in accordance with that reported by other authors. 3,45 In summary, we found that the earliest stage when dynamic SPECT with 123 I-MIBG can detect an abnormality in the LV of SHRs is at 6 months. Dynamic SPECT with 201 Tl can detect perfusion abnormalities in the LV of SHRs at 18 months.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The result indicated that the hypertrophied heart in SHRs becomes heavier during the progression of LVH, which is in accordance with that reported by other authors. 3,45 In summary, we found that the earliest stage when dynamic SPECT with 123 I-MIBG can detect an abnormality in the LV of SHRs is at 6 months. Dynamic SPECT with 201 Tl can detect perfusion abnormalities in the LV of SHRs at 18 months.…”
mentioning
confidence: 61%
“…The result indicated that the hypertrophied heart in SHRs becomes heavier during the progression of LVH, which is in accordance with that reported by other authors. 3,45…”
Section: Discussionmentioning
confidence: 99%